2017
DOI: 10.1007/s10389-017-0828-x
|View full text |Cite
|
Sign up to set email alerts
|

Playground usage and physical activity levels of children based on playground spatial features

Abstract: AimBeing outdoors is one of the strongest correlates of physical activity in children. Playgrounds are spaces especially designed to enable and foster physical activity in children. This study aimed to analyze the relationship between the spatial features of public playgrounds and the usage and physical activity levels of children playing in them.Subjects and methodsA quantitative, observational study was conducted of ten playgrounds in one district of a middle-sized town in Germany. Playground spatial feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(53 reference statements)
1
21
0
1
Order By: Relevance
“…The quality rating scores are presented in Supplementary Table 3 . Quality was rated as high in 28 studies (25.9%) [ 35 , 39 , 40 , 46 , 48 , 53 , 54 , 59 , 61 , 65 , 67 – 70 , 74 , 80 , 82 , 87 , 92 , 101 – 103 , 107 , 115 , 120 , 121 , 130 , 135 ], moderate in 60 studies (56.1%) [ 30 , 32 37 , 40 , 41 , 43 – 48 , 52 , 55 , 56 , 61 – 65 , 70 , 72 – 75 , 77 , 78 , 82 , 84 , 86 , 88 – 91 , 94 , 99 , 101 , 103 , 106 , 108 – 112 , 114 118 , 120 , 122 , 124 , 127 , 128 , 132 , 133 , 135 ], and low in 20 studies (18.7%) [ 33 , 34 , 36 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality rating scores are presented in Supplementary Table 3 . Quality was rated as high in 28 studies (25.9%) [ 35 , 39 , 40 , 46 , 48 , 53 , 54 , 59 , 61 , 65 , 67 – 70 , 74 , 80 , 82 , 87 , 92 , 101 – 103 , 107 , 115 , 120 , 121 , 130 , 135 ], moderate in 60 studies (56.1%) [ 30 , 32 37 , 40 , 41 , 43 – 48 , 52 , 55 , 56 , 61 – 65 , 70 , 72 – 75 , 77 , 78 , 82 , 84 , 86 , 88 – 91 , 94 , 99 , 101 , 103 , 106 , 108 – 112 , 114 118 , 120 , 122 , 124 , 127 , 128 , 132 , 133 , 135 ], and low in 20 studies (18.7%) [ 33 , 34 , 36 ...…”
Section: Resultsmentioning
confidence: 99%
“…In four studies school grade was reported (1st grade, n = 1; 5th grade, n = 2, prekindergarten to 6th grade, n = 1) [47,59,102,113,132]. The quality rating scores are presented in Supplementary Table 3 [39,51,57,62,70,71,74,83,99,100,103,107,108,114,130], of which one observation used both proxy-and selfreported data [102]. Ten studies used accelerometry or pedometry (i.e., device-based measures of physical activity that took place outdoors) [34,35,48,72,77,86…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All ten playgrounds in the district of Petershausen-West were analyzed in this study. Detailed information on quality aspects of the playgrounds and playground users is provided elsewhere [ 45 ]. All procedures performed in this study were in accordance with the ethical standards of the Ethics Committee of the University of Konstanz (IRB15KN01) and with the 1964 Declaration of Helsinki and its later amendments.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, children were assigned to the children’s group when the estimated age was ≤12 years. Detailed information on physical activity levels of children in the playgrounds and playground usage is reported elsewhere [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…If the recreation area is a soccer field, boys are more likely to show more interest than girls and, therefore, it is this group that has the highest level of physical activity. Reimers et al (2017) 28 mentions that there is a relationship between surface area and levels of physical activity in children, but we cannot forget to respond to the needs of physical activity, providing different types of activities to include the participation of all genders. Regarding sedentary lifestyle, MI3 was the group with the highest percentage.…”
Section: Authors' Contributionsmentioning
confidence: 99%